CARMINIC ACID EXTRACTION FROM USING COCHINEAL CLEANER TECHNOLOGY - Erazo, Erazo (2004)
We present a new process for the extraction of carminic acid (ACAR) from cochineal using mass- separating agent R300 (MSA R300) and an organic solvent with affinity only with the ACAR.